Composition of plasmapolymeric coatings using O2/HMDSO gas mixtures and application on elastomers for tribological improvement - Paulkowski, Dominik; Vissing, Klaus; Wilken, Ralph (International Conference on Plasma Surface Engineering, 2013)
Not available